Study on Service Quality and Organizational Performance in Nepalese Local Authorities - Adhikari, Shiva Raj (Journal of Economics and Management, 2025)
The primary aim of this research is to determine the quality management practices that influence organizational performance within the public sector context. A comprehensive survey was conducted across five municipalities, engaging 114 respondents. The collected data were analyzed using regression and correlation techniques alongside descriptive statistical methods to fulfill the research objectives. The findings of this study indicate that service quality significantly impacts organizational performance in Nepalese local government authorities, confirming that quality investments are correlated with enhanced organizational outcomes. Among the service quality dimensions, customer productivity emerged as the most influential predictor of organizational performance, followed by management commitment, internal customer satisfaction, systems, policies and procedures, human resources, and infrastructure.